Civil Law Implications for Children Born Through Surrogacy (Surrogate Mother) - Thalib, Sabrina Riyadh; Marsal, Irsyaf (Dinasti Research, 2025)
This study analyzes the legal status of children born from surrogacy in Indonesia, a practice considered illegal yet a potential solution for infertility, creating a serious rechtsvacuüm. The research objective is a juridical analysis of this issue under Indonesian civil law using a normative juridical method. The findings indicate that surrogacy agreements are legally invalid and considered null and void (van rechtswege nietig) because they fail to meet the